SIFO 1988: Risks - Swedish Institute of Public Opinion Research; Society of Pharmacists (Swedish Institute of Public Opinion Research, 1993)
The Swedish Institute of Public Opinion Research (SIFO) carried out this survey at the request of the Society of Pharmacists. This survey includes questions about the respondents´ opinion on the most serious threats against peoples health and how often she/he thinks of different risks one is exposed to. Other questions deal with confidence in different sources informing about risks. The respondent was also asked about her/his opinion on risks in connection with drug use. Background variables include information on age, housing, size of household, age of members of household, adult children moved out, car ownership, amount of money needed in household, personal income and household income, marital status, education, occupation, employed or self-employed, public or private sector, trade union membership, size of place of work, gender, Swedish citizenship and party preference.

Svenska institutet för opinionsundersökningar (SIFO) utförde undersökningen på uppdrag av Apotekarsocieteten. Frågorna ingick i SIFO-buss B88003/004. Undersökningen innehåller frågor om man uppfattar det som om livet blivit mera riskfyllt än vad det var tjugo år tidigare, vad man upplevde som det allvarligaste hotet mot hälsan och om man ofta tänker på att man kan råka ut för något farligt. En serie frågor berör särskilt inställningen till faran med läkemedel. Respondenterna fick även uppge sin inställning till ett antal påståenden om risker samt ange hur man ser på de risker som finns i tillvaron. Bakgrundsfrågorna tar upp ålder, bostadstyp, hushållets storlek, hushållsmedlemmarnas ålder, vuxna barn som flyttat hemifrån, bilinnehav, hushållets månatliga penningbehov, månadsinkomst, civilstånd, utbildning, hel- eller deltidsarbete, anställd eller företagare, privat eller offentlig tjänst, facklig anslutning, arbetsplatsens storlek, kön, svenskt medborgarskap samt partipreferens.
SIFO 1988: Risker
Keywords: risk; risk; medicinal drugs; läkemedel; hazards; faror; Social Sciences; Samhällsvetenskap; General health and well-being; Allmän hälsa och välbefinnande